Can managed health care help manage health care-associated infections? - Platt, R (Centers for Disease Control and Prevention, 2001)
Managed-care organizations have a unique opportunity, still largely unrealized, to collaborate with health-care providers and epidemiologists to prevent health care-associated infections. Several attributes make these organizations logical collaborators for infection control programs: they have responsibility for defined populations of enrollees and for their overall health, including preventive care; they possess unique data resources about their members and their care; and they are able to make systemwide changes in care. Health care-associated infections merit the attention and effort of managed-care organizations because these infections are common, incur substantial illness and costs, and can be effectively prevented by using methods that are unevenly applied in different health-care settings. Both national and local discussions will be required to enable the most effective and efficient collaborations between managed care organizations and health-care epidemiologists. It will be important to articulate clear goals and standards that can be readily understood and widely adopted.